Analisis Yuridis terhadap Perjanjian Pengalokasian Lahan di Pulau Batam - Rufinus Hutauruk; Lu Sudirman; Ramsen Ramsen (Journal of Judicial Review, 2015)
Rights management is one type of land rights known in Indonesia in addition to property, right to build, right to cultivate, right to use and lease rights. By Right Management, the rights holder has the authority to: plan the allocation and use of land, use the land for the purposes of performing its duties, submit portions of the land to a third party, in accordance with the provisions of the Basic Agrarian Law, and received a cash inflow / replace annual income and money required. Thus authority owned Industrial Development Authority Batam Island (hereinafter referred to Batam Authority) since it was created as an institution that is in charge and responsible for the growth and development of Batam Island as an industrial area (Kep. Interior Minister 43/1977). And the Batam Authority granted management rights over the entire area of land located in Batam Island, including large areas of land in a cluster of islands including the widow Berhias Batam, Tanjung Sau, and nginang and Kasom Island. The purpose of this research is to know and analyzing the: if the substance of the agreement allocating land between Concession Area Agency Batam and PT. Franindo International has met the principle of legal protection and the principle of justice, remedy what can be done if the land allocated Concession Agency Batam area still controlled by the community, and the economic impact if it can not establish physical land in accordance with the development plan. Juridical empirical research methods. Result: The land allocation agreements are made and enforced Regions Batam Exploitation Agency does not meet the principle of legal protection and the principle of fairness, and the recipient sebahagian land allocation can not run the contents of the agreement because there is resistance from the people who control the land.